Desenvolvimento e aplicação de sistema de floco-flotação por ar dissolvido para tratamento da água de lavagem do filtro da ETA Gavião - Chaves, Karina Oliveira (2012)
In Brazil the filter backwash wastewater is normally released in to the water resources without proper treatment, representing a potential danger to the environment. Thus, it is necessary to treat this wastewater in order to dispose it in accordance to federal and state environmental laws. Studies show that Dissolved Air Flotation (DAF) technology has been feasible for this purpose. It is believed that the incorporation of flocculation in curtains and air dissolved flotation system in the same unit can promote high efficiency and significant size reduction, which translates in a technological innovation: the Floculator - Dissolved Air Flotation (FFAD) unit. A FFAD pilot unit was built to evaluate the treatment of Gavião Water Treatment Plant filter backwash wastewater, owned by the Water and Wastewater Company of Ceará (CAGECE). This research had as main objective to quantify and verify the compliance of the filter backwash wastewater parameters to the Resolution No. 430/11 and 357/05 of CONAMA and Ordinance No. 154/2002 of SEMACE. Treatability studies were performed with filter backwash wastewater using Jartest to evaluate the influence of cationic polymer dosages and the feasibility of decreasing flocculation velocity gradients (35 to 5.6 s-1) in the FFAD. Experimental runs of the flocculation - flotation system were performed to evaluate the best polymer dosage and the process parameters such as recirculation rates (TR) and surface application rates (TAS). These parameters were compared by observing the lower residual turbidity and best removal efficiency in the clarified water (AC). The treated wastewater was again characterized using physicalchemical and bacteriological parameters and compared to the specific legislation. The results showed that the use of 1 mg.L-1 of polymer, recirculation rate of 15% and surface application rate of 57 m3.m-2.d-1, presented the highest turbidity efficiency removal (> 98%) and a very stable performance against sudden changes in the influent quality (94.4 to 410UT). It should be noted that the unity showed also a high average efficiency total coliforms removal (98.5%), apparent color removal (97.6%), DOC removal (92.6%), of aluminum (84.1%) removal and turbidity (99.2 %) removal. Given these results, it was concluded that the AC coming from the treatment of ALF by ETA WTP Gavião FFAD met the discharge parameters listed for water resources.